The deceptive absence of Arabic in Nadir Moknèche’s Viva Laldjérie - Ziad Bentahar (Francosphères)
Nadir Moknèche’s Viva Laldjérie (2003) is one of a number of films that mark as well as chronicle the turn of a new leaf in Algeria. It was shot in Algiers at the onset of the twenty-first century, when the previous decade’s civil war meant that images of Algeria on screen had become associated with news of violence rather than movies. As the characters in Viva Laldjérie confront the trauma of war and their personal losses, they speak almost exclusively in French. Arabic remains conspicuously absent except for three specific instances during the film. Outside of these three instances, only a few words are perceived in the background. The circumstances of each use of Arabic indicate an evolution in the characters’ relationships with their pain and suffering following the shock of the war. French, in this context of Algerian civil war, becomes a language that allows a form of detachment from one’s own country for Algerians facing violence.